Regulating Perovskite Crystallization through Interfacial Engineering Using a Zwitterionic Additive Potassium Sulfamate for Efficient Pure‐Blue Light‐Emitting Diodes - Yu, Yi; Wang, Bing‐Feng; Shen, Yang; Su, Zhen‐Huang; Zhang, Kai; Ren, Hao; Zhang, Ye‐Fan; Gao, Xingyu; Tang, Jian‐Xin; Li, Yan‐Qing (Angewandte Chemie International Edition, 2024)
Quasi‐two‐dimensional (quasi‐2D) perovskites are emerging as efficient emitters in blue perovskite light‐emitting diodes (PeLEDs), while the imbalanced crystallization of the halide‐mixed system limits further improvements in device performance. The rapid crystallization caused by Cl doping produces massive defects at the interface, leading to aggravated non‐radiative recombination. Meanwhile, unmanageable perovskite crystallization is prone to facilitate the formation of nonuniform low‐dimensional phases, which results in energy loss during the exciton transfer process. Here, we propose a multifunctional interface engineering for nucleation and phase regulation by incorporating the zwitterionic additive potassium sulfamate into the hole transport layer. By using potassium ions (K+) as heterogeneous nucleation seeds, finely controlled growth of interfacial K+‐guided grains is achieved. The sulfamate ions can simultaneously regulate the phase distribution and passivate defects through coordination interactions with undercoordinated lead atoms. Consequently, such synergistic effect constructs quasi‐2D blue perovskite films with smooth energy landscape and reduced trap states, leading to pure‐blue PeLEDs with a maximum external quantum efficiency (EQE) of 17.32 %, spectrally stable emission at 478 nm and the prolonged operational lifetime. This work provides a unique guide to comprehensively regulate the halide‐mixed blue perovskite crystallization by manipulating the characteristics of grain‐growth substrate. A multifunctional interface engineering is proposed for perovskite crystallization modulation and defect passivation by incorporating a zwitterionic additive potassium sulfamate onto the grain‐growth substrate, leading to pure‐blue perovskite light‐emitting diodes with a champion external quantum efficiency of 17.32 % at 478 nm and spectrally stable CIE chromaticity coordinate of (0.106, 0.129).